Optical Sensor Assembly on knee Brace for continuous knee monitoring application - G. M., Salim; M. A., Zawawi (Springer, 2022)
Purpose: Knee joint is an important part of human body. People with poor knee condition generally have limited physical movement, rendering to mental stress and agony. Current technology to support the knee diagnosis and treatment procedures are limited to the use of manual goniometer, x-ray and magnetic resonance imaging (MRI). Alternative devices with continuous measurement capability for knee monitoring are minimum at this time, mainly due to the difficulties to cover the wide angle of the knee flexion. X-ray and MRI technologies are useful to have some insight on the knee problem, but they are not applicable for continuous monitoring. Aside from being expensive for general use of MRI, x-ray on the other hand can cause short-term side effects due to radiation exposure.